Understanding Postmodernism: Postmodern Culture and Philosophy - Tog’ayev Sarvar Eshniyoz o’g’li; U.Fayzullayeva (Genius Publishing Group, 2023)
Although the word postmodernism was first used in the 1870s, it wasn't until the late 20th and early 21st centuries that it really took off. Supporters of postmodernism dislike categorization, so they are not apt to use the term to describe themselves. But since postmodernists are so prevalent in our society, we all need to have a working knowledge of their philosophy. According to postmodernism, everyone has the freedom to use reason to determine what is true for themselves. Truth used to be a clearly defined truth that each generation tended to embrace. The definition of reality is unclear to postmodernists. When postmodern people seek the truth, they don't rely on what their parents, the government, or the church have taught them; instead, they rely on their own studies, personal experiences, and interpersonal relationships. Postmodernists define reality for themselves, which does not indicate that they do not believe in truth.
Keywords: Postmodern; philosophy; sterile culture; open culture